33 Nutritional programming of puberty in Bos indicus-influenced heifers. (5th December 2019) - Cardoso, Rodolfo C; Williams, Gary L
Abstract: Approximately 5 million beef heifers enter the U.S. cow herd annually and their lifetime productivity is heavily-dependent upon their ability to attain puberty and produce a calf by 24 mo of age. However, a significant proportion of heifers within existing U.S. production systems fail to achieve these goals, particularly in southern regions where Bos indicus-influenced cattle predominate. Therefore, approaches are needed that facilitate nutritional programming of the reproductive neuroendocrine axis, while minimizing feeding costs and optimizing the consistent establishment of puberty by 14–15 mo of age. Increased BW gain between 4 and 9 mo of age facilitates pubertal development by programming hypothalamic centers that regulate GnRH secretion. Among the different metabolic hormones, leptin plays a critical role in conveying nutritional information to the brain and controlling puberty. Two hypothalamic neuronal populations that express the orexigenic peptide neuropeptide Y (NPY) and the anorexigenic peptide alpha melanocyte-stimulating hormone (αMSH) are key components of afferent pathways that convey inhibitory (NPY) and excitatory (αMSH) inputs to GnRH neurons. Our studies have demonstrated that short-term increases in dietary energy intake during juvenile development result in epigenetic, structural, and functional modifications in these hypothalamic pathways to promote high-frequency, episodic release of GnRH/LH. However, integrating the foundational knowledge of metabolic imprinting of the brain for early puberty with issues related to lifetime performance is complex. One approach has been to employ a novel stair-step nutritional regimen involving alternating periods of dietary energy-restriction and re-feeding during juvenile development. This approach is designed to support early onset of puberty by imprinting functional alterations in the hypothalamus during key periods of brain development while optimizing other aspects of growth and performance. Finally, our recent findings suggest that maternal nutrition during gestation can also induce neuroendocrine changes that are likely to persist and influence reproductive performance throughout adulthood in cattle.